Applying online competency-based learning and design-based learning to enhance the development of students’ skills in using PowerPoint and Word, self-directed learning readiness, and experience of online learning - Tsai, Chia-Wen (Universal access in the information society)
Online learning has been widely adopted in higher education, because it can help both teachers and students to achieve educational goals through better accessibility, flexibility, and interaction. As the Internet and educational technologies have evolved, however, educators indicate that online education and the related technology is more than just a technical consideration; thus, online educators and scholars should address the pedagogical perspectives of online learning. Therefore, this study attempts to provide an effective online teaching method and to investigate the effects of online competency-based learning (CBL) and design-based learning (DBL) on enhancing students’ learning performance, self-directed learning readiness (SDLR), and experience of online learning in an online computing course. The experimental design in this study involved a 2 (CBL vs. non-CBL) × 2 (DBL vs. non-DBL) factorial pretest/posttest design. Four classes in a course titled “Applied Information Technology: Office Software” were chosen for this research. Students involved in this experiment were from non-computer field departments at a comprehensive university. Based on the analysis carried out in this research, students who received the intervention with online DBL showed significantly better skills in using PowerPoint. However, learners who received the intervention with online CBL and/or DBL did not have significantly better SDLR or experience of online learning. The potential reasons for this insignificance in students’ SDLR and experience of online learning as well as their implications are reported in this paper.